Chronic granulomatous disease presenting with small bone osteomyelitis in a young child: A case report - Preethi S Chari; Prathap Chandra; Sujay Prasad; Sagar Bhattad (Wolters Kluwer Medknow Publications, 2018)
Chronic granulomatous disease (CGD) is a life threatening inherited disorder with varied clinical presentations often characterized by recurrent bacterial and fungal infections along with widespread granulomatous tissue response. The disease results from phagocytic defects characterized by deficiencies in oxidative burst of neutrophils. Nitroblue tetrazolium reduction test (NBT) and Dihydrorhodamine (DHR) with PMA stimulation by flow cytometry are quick, simple, sensitive and specific laboratory tests that help establish early and reliable diagnosis of CGD with an overall improvement in survival and disease prognosis. We report a case of 2-year old child who presented with small bone osteomyelitis involving bilateral feet and was later diagnosed to have autosomal recessive CGD due to mutation in NCF1 gene.